Quality and economies of scale in higher education: A semiparametric smooth coefficient estimation - Fu, Tsu-tan; Huang, Cliff J; Yang, Yung-lieh (Contemporary economic policy, 2011)
This paper proposes a semiparametric smooth coefficient cost model to study the university cost structure where coefficients are an unknown function of the university's overall quality. A local least square method with a kernel weight function is used to estimate the cost function, and a simple statistic for testing a parametric model of the additive quality versus the semiparametric smooth coefficient model is applied. Empirical results from 56 universities in Taiwan show that, taking quality into account, higher education is subject to diseconomies of scale. In all categories—comprehensive and science/technology and public and private universities—the current university scale in Taiwan is too big to be cost efficient. (JEL I21, H52, 9120)